Análisis de la ejecución del presupuesto público por genérica de gasto del Gobierno Regional de Loreto, periodo 2017 - 2021 - Catashunga Mariño, Lisandro (2023)
The execution of the public budget is an important indicator that allows us to measure the spending capacity of a state entity in the development of its activities during a given period, as well as whether or not the established objectives and goals have been met. The present investigation is entitled "Analysis of the Execution of the Public Budget by General Expenditure of the Regional Government of Loreto, period 2017 - 2021", its objective is to determine the level of execution that the aforementioned public budget presents in the aforementioned study period. The research was of a quantitative type and a non-experimental - longitudinal descriptive design. Finally, after analyzing the data, it was possible to determine that the public budget by generic expense presents a high level of execution, that is, 91.82%, which is equivalent to S/9'762,222,992.